2016
DOI: 10.1007/s10162-016-0581-9
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Cochlear Mechanics and Performance of Temporal Fine Structure-Based Tasks

Abstract: This study examined whether the mechanical characteristics of the cochlea could influence individual variation in the ability to use temporal fine structure (TFS) information. Cochlear mechanical functioning was evaluated by swept-tone evoked otoacoustic emissions (OAEs), which are thought to comprise linear reflection by micromechanical impedance perturbations, such as spatial variations in the number or geometry of outer hair cells, on the basilar membrane (BM). Low-rate (2 Hz) frequency modulation detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…This finding likely extends to simple frequency discrimination, which is believed to rely on the same mechanism as slow FM (Sęk and Moore, 1995). A unitary code for FM and AM at all rates also helps explain the generally high-multicollinearity between FM and AM sensitivity observed here ( Figure 3) and in several previous studies with normal-hearing listeners (Whiteford and Oxenham, 2015;Otsuka et al, 2016;Paraouty and Lorenzi, 2017;, although the effect size of the correlation between slow-rate FM and AM was smaller than observed in previous studies. It may also help explain why attempts to improve speech and music perception by reintroducing fine timing cues via electrical pulses in cochlear implants have not been successful (Zeng et al, 2005;Schatzer et al, 2010).…”
Section: A Unitary Code For Fmsupporting
confidence: 72%
See 1 more Smart Citation
“…This finding likely extends to simple frequency discrimination, which is believed to rely on the same mechanism as slow FM (Sęk and Moore, 1995). A unitary code for FM and AM at all rates also helps explain the generally high-multicollinearity between FM and AM sensitivity observed here ( Figure 3) and in several previous studies with normal-hearing listeners (Whiteford and Oxenham, 2015;Otsuka et al, 2016;Paraouty and Lorenzi, 2017;, although the effect size of the correlation between slow-rate FM and AM was smaller than observed in previous studies. It may also help explain why attempts to improve speech and music perception by reintroducing fine timing cues via electrical pulses in cochlear implants have not been successful (Zeng et al, 2005;Schatzer et al, 2010).…”
Section: A Unitary Code For Fmsupporting
confidence: 72%
“…Another alternative interpretation is that a dual code, based on combined place and timing cues, accounts for slow FM sensitivity, rather than a unitary code. A dual code could potentially explain the high collinearity often observed between measures of FM and AM sensitivity (Whiteford and Oxenham, 2015;Otsuka et al, 2016;Paraouty and Lorenzi, 2017;, as well as the observation from experiment 1 that slow-rate FM sensitivity may not be as strongly correlated to AM sensitivity as fast-rate FM (although these differences in correlation strength were not statistically significant). In addition, it has been found that AM can interfere with the detection of FM, particularly at fast rates and high carrier frequencies, perhaps pointing to the possibility of a dual code (Moore and Sęk, 1996;Ernst and Moore, 2010;King et al, 2019).…”
Section: Alternative Interpretationsmentioning
confidence: 99%
“…A few recent studies have used correlational measures in NH listeners to examine what peripheral code may be responsible for low-frequency carrier FM and have found conflicting evidence for the presence of TFS coding (e.g., Whiteford and Oxenham 2015;Otsuka et al 2016;Paraouty and Lorenzi 2017). These studies have revealed high multicollinearity across modulation-detection tasks, including those thought to use separate mechanisms (e.g., low-carrier, slowrate FM, and slow-rate AM).…”
Section: Introductionmentioning
confidence: 99%
“…TE is coded in the cochlea as the probability of auditory neuron firing given the amplitude of displacement at a cochlear place, and phase locking to the TE has been observed throughout the cochlea and maintained to the auditory cortex. 74,75 Information in acoustic signals is conveyed primarily through changes in amplitude as a function of frequency over time, and TE represents this information after an initial stage of cochlear filtering. Many basic auditory features rely on TE local to a specific frequency region, including loudness, pitch and source location, and auditory object formation.…”
Section: Temporal Resolution In Severe Hearing Lossmentioning
confidence: 99%